Dynamic in vitro gastric digestion behaviour of camel milk - Li S; Ayyash M; Ye A; Singh H (Elsevier Ltd, 2023)
This study investigated the dynamic in vitro gastric digestion behaviour of camel milk. Coagulum that was retainable in the stomach was not formed during the digestion of camel milk, whereas bovine milk reconstituted to the same protein concentration (2.9%, w/w) underwent pronounced gastric coagulation into structured clots. During early digestion, the camel milk formed small particles, resulting from its weak coagulation, that were preferentially emptied from the stomach. These particles became more compact and spherical in the first hour of digestion and then gradually decreased in size. Protein analysis indicated that the main camel milk proteins were digested in the order αS1-casein > β-casein > α-lactalbumin, which may have been modulated by the decreasing pH during the dynamic gastric digestion. This unique coagulation behaviour of camel milk resulted in its rapid gastric digestion and emptying, which may have nutritional implications.